PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS X MIA 4 SMA NEGERI 5 PEKANBARU - Delfita, Ovemy; ', Kartini; ', Sakur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is a class action research. This research aims to improve the learning process and improve learning result in mathematics in grade X MIA 4 of SMA Negeri 5 Pekanbaru by applying the Discovery Learning model. The subject of this research were the students in the class X MIA 4 of SMA Negeri 5 Pekanbaru that consist of 19 boys and 21 girls at the second semester of academic year 2016/2017. Implementation of the learning process before held action, there is a problem of learning that is still focused on the teacher so that students can not find the concept of learning. To solve this problem requires a learning model where students can actively discover teir own learning concepts. The instruments of data collection in this research were observation sheets and students mathematic tests. The observation sheets were analyzed in desciptive narative, while the students’ mathematic tests were analyzed in statistic desciptive. The descriptive showed an improvement of learning process prior to the action on the first and second cycles and improve the students’ achievement of learning mathematic in grade X MIA 4 of SMA Negeri 5 Pekanbaru in the second semester academic years 2016/2017.Keywords : Students’ Math Achievement, Discovery Learning Model, Clasroom Action Research.